1982
DOI: 10.1007/bf00543759
|View full text |Cite
|
Sign up to set email alerts
|

Structure property studies of fibres from various parts of the coconut tree

Abstract: Fibres from different structural parts of the coconut palm tree (Cocos nucifera, linn.) have been examined for properties such as size, density, electrical resistivity, ultimate fracture mode, microfibrillar angle as well as cellulose and lignin contents of these fibres have been determined. The observed properties have been related to the internal structure and chemical composition of the fibres. Some potential uses of these fibres have been I isted .tensile strength, initial modulus and percentage elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(94 citation statements)
references
References 5 publications
3
86
0
5
Order By: Relevance
“…They also suggested that natural fibre can be used as a replacement for wood in insulating applications. Further study reported by another researcher on electrical resistivity of various part of the coconut tree and confirm that it can used as good insulators (Satyanarayana et al 1982). Recently electrical properties of oil palm fibres reported and concluded that dielectric constant value of oil palm fibre is in agreement with the values reported earlier (Chand 1992) for other natural fibres (Shinoj et al 2010).…”
Section: Electrical Properties Of Oil Palm Fibre Based Hybrid Compositessupporting
confidence: 63%
“…They also suggested that natural fibre can be used as a replacement for wood in insulating applications. Further study reported by another researcher on electrical resistivity of various part of the coconut tree and confirm that it can used as good insulators (Satyanarayana et al 1982). Recently electrical properties of oil palm fibres reported and concluded that dielectric constant value of oil palm fibre is in agreement with the values reported earlier (Chand 1992) for other natural fibres (Shinoj et al 2010).…”
Section: Electrical Properties Of Oil Palm Fibre Based Hybrid Compositessupporting
confidence: 63%
“…Regenerated cellulose of compound 3 has higher cellulose content. Hence, higher crystallinity and higher flexural strength are attained [10] so it is unlikely for compound 3 to get tangled. The results of fiber content are represented in Figure 3 in terms of the change in fiber content with respect to the average content.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the leafsheath consists of three distinct types of multicellular fibres made of mostly cellulose and lignin arranged in a highly ordered structure. The mechanical properties of these three types of leaf-sheath fibres are different from each other [106]. Wood and bamboo are excellent examples of natural fibrous composites with high work of fracture.…”
Section: Diverse Use Of Fibresmentioning
confidence: 99%
“…The coir fibre derived from its seed husk is well-known and used in floor coverings, mattress fillings and others. Among other fibres found on a coconut palm [105], the layers of fibrous sheets in the leaf-sheath (base of the leaf stalk attached to the tree trunk) with fibres in the alternating sheets oriented nearly orthogonal to each other appear to be already in a woven structure [106]. Interestingly, the leafsheath consists of three distinct types of multicellular fibres made of mostly cellulose and lignin arranged in a highly ordered structure.…”
Section: Diverse Use Of Fibresmentioning
confidence: 99%